Development of a core outcome set for open lower limb fracture; what core outcomes should be measured - Aquilina, A; Claireaux, H; Tutton, E; Costa, M; Fitzpatrick, R; Griffin, X (British Editorial Society of Bone and Joint Surgery, 2023)
Aims: Open lower limb fracture is life-changing, resulting in substantial morbidity and resource demand, while inconsistent outcome-reporting hampers systematic review and meta-analysis. A core outcome set establishes consensus among key stakeholders for the recommendation of a minimum set of outcomes. This study aims to define a core outcome set for adult open lower limb fracture.